Efforts to Improve Children's Speaking Skills Through the Reading Aloud Method at RA Ar-Rahman - Widiarti, Wida; Afriyanti, Widhi; Widayanti; Widati; Widanarti (MANDAILING GLOBAL EDUKASIA, 2024)
Early age is a child with an age range of 0-6 years who must be stimulated in their developing body abilities, including the ability in language skills. This period is the right time to apply various aspects of child development, one of which is the aspect of children's language skills in speaking. In this era of globalization, the phenomenon that occurs in the field, especially at RA Ar-Rahman, is that most parents who entrust their children to the RA Ar-Rahman institution are motivated because children cannot be separated from gadgets, so that children's language development is delayed and not yet fluent in speaking. There are many methods that can stimulate children's speaking skills, one of which is by applying the reading aloud method. The purpose of this study is to increase the speaking skills of group A children by using the reading aloud method at RA Ar-Rahman. The steps used in this study are Classroom Action Research which is carried out through two stages of research, the first study was carried out 5 times for improvement. And the target of the study was children aged 4 to 5 years, totaling 19 children. The data collection technique used was observation sheets and documentation in order to obtain an overview of information about children's speaking abilities. The results of the study in children's speaking abilities increased to 95%. It can be concluded that the reading aloud method has a significant influence in improving the speaking ability of children aged 4-5 years